The Asnaf Zakat Entrepreneurship Research Trend: A Systematic Literature Review - Ikmal Hafiz Jamal; Mohd Afandi Mat Rani; Mohd Izzat Amsyar Mohd Arif; Faezy Adenan; Norazlina Mamat (USIM PRESS, 2024)
VOL. 34 NO. 3 (2022)